FACTORS INFLUENCING THE ATTITUDES AND DECISIONS OF LOWER CLASS COMMUNITIES IN USING ISLAMIC BANK MOBILE BANKING - Muhammad Nur Tanjung; Abdul Nasser Hasibuan; Utari Evy Cahyani (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to analyze the factors influencing the attitudes and decisions of lower-class communities in adopting Islamic bank mobile banking services, with a specific focus on the BSI Mobile application. The research applies the Technology Acceptance Model (TAM) developed by Davis (1989), emphasizing two key constructs—perceived ease of use and perceived usefulness—as determinants of users’ attitudes and decisions. The study employs a quantitative approach using a survey method involving 100 lower-class customers of Bank Syariah Indonesia (BSI) Sibuhuan. Data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) technique through SmartPLS 4.0 software. The results indicate that perceived usefulness significantly affects both attitude and decision to use, while perceived ease of use influences attitude indirectly. The R² value for attitude (0.743) and decision (0.654) shows that the model has strong explanatory power. These findings reveal that lower-income customers are more motivated by perceived benefits, such as convenience, time efficiency, and transaction security, rather than interface simplicity. From a practical perspective, the study suggests that Islamic banks should strengthen digital literacy, user assistance, and customer trust to enhance mobile banking adoption among lower-class communities.